Strategic priorities of regional economic development in the context of regulating non-monetary factors of inflation - Dvoryadkina, Elena; Kuklinova, Polina (Upravlenec (Online), 2024)
A vast array of research works concentrates on such aspects of inflation processes as their essence, development factors, anti-inflationary regulation, etc., but precious few of them attempt to identify the factors of inflation in the strategic priorities of regional development. At the same time, economics and state policy at both national and regional levels recognise the significant effect of inflation on economic development. The paper deals with non-monetary factors of inflation in regions and develops a path for formulating regional policy on their regulation. The theories of regional economic development and inflation constitute the methodological framework of the study. The research methods include systematization, functional and comparative analysis, deduction. We identify the provisions of the socio-economic development strategies of the Ural macroregion’s member territories relating to the regulation of non-monetary factors in the development of inflationary processes. The identified aspects of inflation reflect the impact of its non-monetary factors on regional economic development and require anti-inflationary policy to be coupled with the areas of activity of regional authorities. We present a conceptual-logical model for framing regional policy on regulating non-monetary factors of inflation in an RF subject specifying the strategic priorities of economic development that influence regional factors of inflation. The model demonstrates that it is the state programmes of Russia’s constituent entities that are the main tool for regulating non-monetary factors of inflation in the regional government system. It coordinates price regulation measures in the regions with the goals and objectives of policy aimed at developing their economies. The findings contribute to the understanding of regional inflation factors and can be used by regional authorities when executing socio-economic development strategies.